2021
DOI: 10.3390/rs13142731
|View full text |Cite
|
Sign up to set email alerts
|

Combining Multiple Geospatial Data for Estimating Aboveground Biomass in North Carolina Forests

Abstract: Mapping and quantifying forest inventories are critical for the management and development of forests for natural resource conservation and for the evaluation of the aboveground forest biomass (AGFB) technically available for bioenergy production. The AGFB estimation procedures that rely on traditional, spatially sparse field inventory samples constitute a problem for geographically diverse regions such as the state of North Carolina in the southeastern U.S. We propose an alternative AGFB estimation procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Further, for land use and land cover analysis, Crop Data Layer (CDL) and the National Land Cover Database (NLCD) are two primary datasets in the US. Recent research has shown CDL to have greater precision than the NLCD [19]. As a result, we have chosen to rely on CDL raster-formatted data for subsequent analysis.…”
mentioning
confidence: 99%
“…Further, for land use and land cover analysis, Crop Data Layer (CDL) and the National Land Cover Database (NLCD) are two primary datasets in the US. Recent research has shown CDL to have greater precision than the NLCD [19]. As a result, we have chosen to rely on CDL raster-formatted data for subsequent analysis.…”
mentioning
confidence: 99%